2015
DOI: 10.1007/s11596-015-1436-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of patients with adenosquamous lung carcinoma

Abstract: This study was aimed to characterize clinicopathological features and prognosis of patients with adenosquamous lung carcinoma (ASC). Among the 2531 patients with lung cancer who underwent surgery between January 2000 and June 2012 in our hospital, 59 were histologically diagnosed as having ASC. The clinicopathological features and follow-up data of ASC patients were collected and analyzed statistically. Superior lobectomy was accomplished in 40 patients, middle and inferior lobectomy in 3, lobectomy plus parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…LASC, with balanced adenomatous and squamous components, was associated with better survival outcomes than those with one predominant component [9,17]. However, in contrast to these results, some authors also observed that SCC-predominant histology represents a better prognosis of ASC [18]. Therefore, further research on this topic is warranted.…”
Section: Variables Hr (95%)mentioning
confidence: 82%
“…LASC, with balanced adenomatous and squamous components, was associated with better survival outcomes than those with one predominant component [9,17]. However, in contrast to these results, some authors also observed that SCC-predominant histology represents a better prognosis of ASC [18]. Therefore, further research on this topic is warranted.…”
Section: Variables Hr (95%)mentioning
confidence: 82%
“…Adenosquamous (ADSCC) disease accounts for 2–3% of all diagnoses, though this diagnosis can only be made with wedge biopsy or tumour resection, which could lead to underestimation of its prevalence in patient populations34. ADSCC is a particularly poor prognosis tumour type56, and genetic studies have demonstrated that both histological components share mutations, suggesting a monoclonal tumour origin7. Notably, in many cases of disease progression after targeted therapy for EGFR mutation, when it is clinically justifiable to take a second biopsy, conversion of ADC to SCC has been observed8.…”
mentioning
confidence: 99%
“…A previous study found that the amount of adenocarcinoma components did not affect the survival rate, while another reported that adenocarcinoma predominant tumors were considered to be a worse prognostic factor [ 18 - 20 ]. Conversely, Gawrychowski et al observed that a balance of squamous and adenocarcinoma components had better prognosis than either being predominant [ 17 ].…”
Section: Discussionmentioning
confidence: 99%